Clinical and morphological portrait of tumors with microsatellite instability - A. A. Musaelyan; V. D. Nazarov; A. S. Budnikova; S. V. Lapin; S. L. Vorobyev; V. L. Emanuel; A. A. Zakharenko; S. V. Orlov (Успехи молекулярной онкологии, 2021)
Background. Microsatellites are short tandem nucleotide repeats, the change in length of which plays a key roles in the pathogenesis of various malignant neoplasms. This change is called microsatellite instability. It is caused by aberrations in the genes of DNA mismatch repair system. Tumors with microsatellite instability are a special subtype regardless of location and are characterized by high sensitivity to immune checkpoint inhibitors.Objective – determination of characteristic clinical and morphological patterns of tumors of various localizations with microsatellite instability.Materials and methods. The study included 512 patients with malignant tumors of different localizations. Of these, 359 patients were diagnosed with colorectal cancer, 57 with uterine body cancer, and 57 with stomach cancer. Determination of the status of microsatellite instability was performed by a PCR-based method using 5 mononucleotide markers: BAT-25, BAT-26, NR-21, NR-24, NR-27.Results. The prevalence of microsatellite instability in colorectal cancer, uterine neoplasm and gastric cancer was 6.4; 22.8 and 1.75 %, respectively. Patients with MSI-positive colorectal cancer are characterized by yonger age (p = 0.023), right-sided localization of the tumor (p <0.0001), presence of multiple primary tumors (p = 0.0299), poorly differentiation (p = 0.0025), mucinous component (p <0.0001), tumor-infiltrating lymphocytes (p <0.0001) and Crohn-like reaction (p = 0.0006). Patients with uterine neoplasms with microsatellite instability are characterized by the presence of endometrial adenocarcinoma (p = 0.047), as well as the presence of tumor-infiltrating lymphocytes (p = 0.0022) and cribriform growth (p = 0.0011).Conclusion. A common pattern for colorectal cancer and uterine neoplasms is the presence of tumor-infiltrating lymphocytes. Certain clinical and morphological features of tumors of these localizations will more accurately identify candidates for microsatellite instability status determination for further immunotherapy.